Sodium-Glucose Transport Protein 2 Inhibitors Association with Euglycemic Diabetic Ketoacidosis - Caroline Wojtas; Alex P. Rasarmos; Naja Naddaf (Case Reports in Endocrinology)
Diabetic ketoacidosis (DKA) is a life-threatening medical emergency that occurs in both type 1 and type 2 diabetes mellitus. Here, we describe the case of a 49 year-old male patient with type 2 diabetes mellitus who presented to the emergency department with complaints of epigastric abdominal pain and intractable vomiting. He had been on sodium-glucose transport protein 2 inhibitors (SGLT2i) for 7 months. Considering the clinical exam and lab findings with a glucose level of 229, a diagnosis of euglycemic DKA was made. He was treated according to DKA protocol and discharged. The relationship between SGLT2 inhibitors and euglycemic DKA remains to be explored; given the absence of clinically significant hyperglycemia during the presentation, a delay in diagnosis may be observed. After an extensive literature review, we introduce our case presentation in the setting of gastroparesis in comparison to previous reports and suggest future improvements in terms of early clinical suspicion for euglycemic DKA.